Expression of inflammatory cytokines in serum and peritoneal fluid from patients with different stages of endometriosis. (3rd June 2018) - Fan, Yan-Yan; Chen, Hong-Yu; Chen, Wei; Liu, Yi-Nan; Fu, Yan; Wang, Li-Na
Abstract: Objective: To investigate the level of inflammatory cytokines in endometriosis patients, and explore the relationship between IL-37 concentration and endometriosis stages. Methods: Inflammatory cytokine concentrations from 27 patients with different stages of endometriosis and 52 controls without endometriosis were examined by ELISA. Then, the specificity and sensitivity of cytokines for distinguishing from controls and the different stages of endometriosis were analyzed using the ROC curve. Results: The difference in serum concentrations of IL-37, IL-17A, IL-10, and IL-2 between the endometriosis and control groups was statistically significant ( p < .01). Compared with controls, significantly higher levels of serum IL-37 and IL-10, and significantly lower levels of serum IL-17A and IL-2 were detected in patients with endometriosis ( p < .01). Furthermore, IL-2 concentration was significantly higher in peritoneal fluid (PF) in the endometriosis group ( p = .0034), IL-10 concentrations in PF were significantly lower in the early-stages of endometriosis than in the more advanced groups ( p = .0439), and IL-4 concentration in PF was significantly higher in more advanced endometriosis ( p = .0228). The sensitivity and specificity of serum IL-37 for distinguishing endometriosis were 81.48% and 83.33%, respectively, and the cutoff concentration was 69.84 pg/ml. For IL-17A, the sensitivity and specificity were 96.30% and 100%, respectively, and the cutoff concentration was 57.54 pg/ml. For IL-10, the sensitivity and specificity was 92.59% and 100%, respectively, and the cutoff concentration was 3.301 pg/ml. For IL-2, the sensitivity and specificity were 74.07% and 93.75%, respectively, and the cutoff concentration was 1.813 pg/ml. For PF IL-2, the sensitivity and specificity were 29.73% and 100%, respectively, and the cutoff concentration was 1.06 pg/ml. Conclusions: IL-37, IL-17A, IL-10, and IL-2 may play a significant role in immune response in endometriosis. IL-37 levels may be used as a diagnostic marker for endometriosis.